Branding and Packaging Training to Improve Product Promotion at MSMEs in Mojosari Village - Maidah, Firdaus Al; Rizki, Via Lailatur; Putri, Nur Latifa Isnaini (IMPOWERMENT SOCIETY, 2023)
As with micro business products in general, Micro Small and Medium Enterprises (MSME) entrepreneurs encounter several problems while developing their businesses, especially in increasingly fierce competition in this globalization era. This community service aims to help MSME entrepreneurs in Mojosari Village, Lumajang Regency East Java, overcome the difficulties they encounter due to globalization. Activities carried out in this program include site surveys, interviews and discussions with MSME entrepreneurs, holding training on branding and packaging, monitoring, and evaluation. This community service program has produced several outcomes. The first outcome is establishing increasingly solid collaboration between MSME entrepreneurs in Mojosari Village. This collaboration will help MSME entrepreneurs with better and more up-to-date business knowledge and skills to keep up with the times and technology. The second outcome is that this program can produce skilled and qualified personnel in their fields, which is realized by creating unique and attractive branding, labels, and packaging.